Medieval single women the politics of social classification in late medieval England - Beattie, Cordelia (Oxford University Press, 2007)
In a culture in which marriage was the desirable norm, and virginity was particularly prized in females, the categories 'virgin' and 'widow' held particular significance. This book investigates the uses of the category 'single woman'.